Exploration and conservation of bacterial genetic resources as bacteriocin producing inhibitory microorganisms to pathogen bacteria in livestock - Chotiah S (Indonesian Center for Animal Research and Development (ICARD), 2013)
Exploration and conservation of microorganisms producing bacteriocin was done as the primary study towards the collection of potential bacteria and its application in improving livestock health condition and inhibit food borne pathogens. Diferent kinds of samples such as beef cattle rectal swab, rumen fluids, cow’s milk, chicken gut content, goat’s milk were collected at Bogor cattle slaughter houses, poultry slaughter houses, dairy cattle and goat farms. A total of 452 bacterial isolates consisted of 73 Gram negative bacteria and 379 Gram positive bacteria were isolated from samples collected and screened for bacteriocin activity. Determination of bacteriocin activity with bioassay using agar spot tests were carried out on liquid and semisolid medium assessing 8 kins of indicators of pathogenic bacteria and food borne pathogens. A total of 51 bacteriocin producing strains were collected and some of the strains had high inhibitory zone such as Lactobacillus casei SS14C (26 mm), Enterobacter cloacae SRUT (24mm), Enterococcus faecalis SK39 (21mm) and Bifidobacterium dentium SS14T (20mm) respectively, to Salmonella typhimurium BCC B0046/ATCC 13311, E. coli O157 hemolytic BCC B2717, Listeria monocytogenes BCC B2767/ATCC 7764 and Escherichia coli VTEC O157 BCC B2687. Evaluation after conservation ex situ to all bacterocin producing strain at 5oC for 1 year in freeze drying ampoules in vacuum and dry condition revealed the decreasing viability starting from log 0.8 CFU/ml for Lactococcus and Leuconostoc to log 2.2. CFU/ml for Streptococcus. Result of the study showed that the bacteriocin producing strains obtained were offered a potential resource for preventing disease of livestock and food borne diseases. Key Words: Bacterocin, Bacteria, Exploration, Conservation Ex Situ